Blocking Thrombin Significantly Ameliorates Experimental Autoimmune Neuritis - Shavit-Stein, Efrat; Aronovich, Ramona; Sylantiev, Constantin; Gera, Orna; Gofrit, Shany G.; Chapman, Joab; Dori, Amir (Frontiers in Neurology, 2019)
Thrombin and its protease-activated receptor 1 (PAR1) are potentially important in peripheral nerve inflammatory diseases. We studied the role of thrombin and PAR1 in rat experimental autoimmune neuritis (EAN), a model of the human Guillain-Barre syndrome (GBS). EAN was induced by bovine peripheral myelin with complete Freund’s adjuvant (CFA). Thrombin activity in the sciatic nerves, clinical scores and rotarod performance were measured. Thrombin activity in the sciatic nerve was elevated in EAN compared to CFA control rats (sham rats) (p≤0.004). The effect of blocking the thrombin-PAR1 pathway was studied using the non-selective thrombin inhibitor N-Tosyl-Lys-chloromethylketone (TLCK), and the highly specific thrombin inhibitor N-alpha 2 naphtalenesulfonylglycyl á-4 amidino-phenylalaninepiperidide (NAPAP(. In-vitro TLCK and NAPAP significantly inhibited specific thrombin activity in EAN rats sciatics (p<0.0001 for both inhibitors). Treatment with TLCK 4.4mg/kg and NAPAP 69.8mg/kg significantly improved clinical and rotarod scores starting at day 12 and 13 post immunization (DPI12, DPI13) respectively (p<0.0001) compared to the untreated EAN rats. In nerve conduction studies, proximal amplitude was significantly lower in EAN compared to sham rats (0.76±0.34 vs. 9.8±1.2, mV, p<0.0001). Nerve conduction velocity was impaired in EAN rats (23.6±2.6 vs. sham 43±4.5, m/sec p=0.01) and was normalized by TLCK (41.2±7.6 m/sec, p˂0.05). PAR1 histology of the sciatic node of Ranvier indicated significant structural damage in the EAN rats which was prevented by TLCK treatment. These results suggest thrombin-PAR1 pathway as a possible target for future intervention in GBS.